2015
DOI: 10.1016/j.vaccine.2015.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of vaccination in India for children aged 12–36 months

Abstract: India's immunization coverage remained low in 2008, with just slightly more than half of all children aged 12-36 months fully vaccinated with UIP-recommended vaccines. A better understanding of the predictors for vaccination can help shape interventions to reduce disparities in full vaccination among children of differing demographic/cultural groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 22 publications
6
34
1
2
Order By: Relevance
“…However, the reports of incomplete vaccination schedules is comparable with that of the Ambo and Yaya-Gulelena Ad/Libanos district, Ethiopia [11]. On the other hand, the proportion of fully vaccinated children in this study is lower than the report from Sinana district, southeast Ethiopia [14], 2016 EDHS [8], India [15], Bangladesh DHS [16] and Umraniye, a district of Istanbul, Turkey [17]. The variation may be due to a difference in study participants' characteristics.…”
Section: Discussionsupporting
confidence: 47%
“…However, the reports of incomplete vaccination schedules is comparable with that of the Ambo and Yaya-Gulelena Ad/Libanos district, Ethiopia [11]. On the other hand, the proportion of fully vaccinated children in this study is lower than the report from Sinana district, southeast Ethiopia [14], 2016 EDHS [8], India [15], Bangladesh DHS [16] and Umraniye, a district of Istanbul, Turkey [17]. The variation may be due to a difference in study participants' characteristics.…”
Section: Discussionsupporting
confidence: 47%
“…Individual, household and regional characteristics having a previously reported association with children's vaccination status and with complete data available in the survey datasets were chosen for analysis. Individual characteristics included child-specific characteristics such as gender, age in months and place of birth and maternal characteristics such as mother's age at childbirth, educational attainment, antenatal participation and maternal tetanus vaccination [20][21][22][23]. In addition, caste and religious preference of the head of household were selected [22,24].…”
Section: Socio-demographic Variablesmentioning
confidence: 99%
“…Individual characteristics included child-specific characteristics such as gender, age in months and place of birth and maternal characteristics such as mother's age at childbirth, educational attainment, antenatal participation and maternal tetanus vaccination [20][21][22][23]. In addition, caste and religious preference of the head of household were selected [22,24]. Household characteristics included urban or rural location and in the absence of a readily available wealth index measure (for DLHS-1), type of dwelling (Mud, semi-cemented or cemented) was used as a proxy measure of household wealth.…”
Section: Socio-demographic Variablesmentioning
confidence: 99%
“…Some studies show that the number religious exemptions has been increasing (18), leading to vaccine preventable disease outbreaks (10) such as mumps outbreak in a protestant orthodox group in The Netherlands. Shrivastwa et al (19) found religion as predictive factor of children’s vaccination status in India. Compared to Hindus, Muslim children had greater chance of being under-vaccinated or unvaccinated compared with the vaccinated children.…”
mentioning
confidence: 99%